2019
DOI: 10.3389/fpls.2019.01138
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Barley Leaf Epidermis and Extrahaustorial Proteomes During Powdery Mildew Infection Reveals That the PR5 Thaumatin-Like Protein TLP5 Is Required for Susceptibility Towards Blumeria graminis f. sp. hordei

Abstract: Powdery mildews are biotrophic pathogens causing fungal diseases in many economically important crops, including cereals, which are affected by Blumeria graminis. Powdery mildews only invade the epidermal cell layer of leaf tissues, in which they form haustorial structures. Haustoria are at the center of the biotrophic interaction by taking up nutrients from the host and by delivering effectors in the invaded cells to jeopardize plant immunity. Haustoria are composed of a fungal core delimited by a haustorial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 86 publications
(127 reference statements)
3
18
0
Order By: Relevance
“…Leaf senescence-related changes in the secretome, along with variations in the AF volume and pH resemble pathogen attack responses, that in turn involve the induction of many Senescence Associated Genes, SAGs genes (Little et al, 2007;Schippers et al, 2015). PR5 markedly accumulates in the apoplast in response to a variety of biotic and abiotic stresses (Piofczyk et al, 2015;Lambertucci et al, 2019), suggesting a role in a possible universal stress response, or in a crosstalk point where different stress responses converge. It would be plausible that stress-related and senescence programs trigger common mechanisms under conditions requiring recycling.…”
Section: Discussionmentioning
confidence: 99%
“…Leaf senescence-related changes in the secretome, along with variations in the AF volume and pH resemble pathogen attack responses, that in turn involve the induction of many Senescence Associated Genes, SAGs genes (Little et al, 2007;Schippers et al, 2015). PR5 markedly accumulates in the apoplast in response to a variety of biotic and abiotic stresses (Piofczyk et al, 2015;Lambertucci et al, 2019), suggesting a role in a possible universal stress response, or in a crosstalk point where different stress responses converge. It would be plausible that stress-related and senescence programs trigger common mechanisms under conditions requiring recycling.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, GRMZM2G154449 encoding a Thaumatin-like protein (TLP), was predicted to be targeted by Rhi-milR-4104-5p. Previous studies have revealed that plant TLP is classified into the PR protein family 5 (PR5) and exhibits an antifungal property [46]. These results indicated that Rhi-milR-4104-5p may negatively regulate resistance of maize by targeting TLP genes.…”
Section: Predicting the Targeted Host Genes For Va Milrnasmentioning
confidence: 98%
“…Chitinases, which we also found overexpressed at this timepoint, are secreted by the host cell to degrade fungal walls and elicit PAMP-triggered immunity (PTI) through chitin recognition (Pusztahelyi, 2018). Accumulation of chitinases has also been reported in the extra-haustorial complex during Bgh infection (Lambertucci et al, 2019). Similarly, other protein families that were also reported in the extrahaustorial complex were also found as DM DE at 32 HAI including genes associated with the TCA cycle and pyruvate metabolism, germin-like protein, and cysteine synthase.…”
Section: Integration Of Eqtl and Interactome Data Predicts Disease Modules During Bghmentioning
confidence: 60%
“…Similarly, other protein families that were also reported in the extrahaustorial complex were also found as DM DE at 32 HAI including genes associated with the TCA cycle and pyruvate metabolism, germin-like protein, and cysteine synthase. Genes involved in pyruvate metabolism are upregulated during haustorial development to contribute to energy production in defense and provide with precursors of other signaling pathways (Qiu et al, 2020;Lambertucci et al, 2019). Remarkably, among this group there is also a malate dehydrogenase (HORVU.MOREX.r2.1HG0067490) that was characterized as target of the Bgh effector BEC1054/CSEP0064 (Pennington et al, 2016).…”
Section: Integration Of Eqtl and Interactome Data Predicts Disease Modules During Bghmentioning
confidence: 99%
See 1 more Smart Citation